DIGITALIZATION OF PRODUCTION AND BUSINESS PROCESSES IN THE AGRICULTURAL SECTOR OF THE ECONOMY - CHUIENKO, VITALII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article defines the concepts of production and business processes, which are the basis of enterprises' activities and ensure their functioning in the context of digitalization. The simplest business processes that represent the transition from traditional paper documents to electronic ones and use modern information technologies are considered. Successful digitalization is possible under the following conditions: provision of institutions, enterprises and organizations with computer equipment; availability of trained personnel working with digital technologies; and access to the Internet and digital resources. The main focus is on the practical aspects of digitalization of business processes, as digitalization has become an integral part of modern life. Digitalization is being implemented in all areas of activity, including the agricultural sector, which ensures the country's food security and needs to increase its export potential.The ideas and opinions of scientists from different countries of the world regarding the implementation of digital technologies in all business processes of enterprises to ensure production efficiency and competitiveness are summarized.The article discusses how changes in the development of human civilization have led to the transition to digital technologies, which have become an integral part of business processes.  Business processes are constantly changing, they are aimed at continuous improvement and require the introduction of new technologies and approaches. And one of the most important components of this process is digital development, which is characterized by constant forward movement. Once one goal is achieved, another task arises, and its solution is an opportunity for growth. To ensure that scientific knowledge continues to develop, it is necessary to systematize and analyze information on the digitalization of business processes at enterprises. This will allow us to better understand this process, its impact on the economy and society, and develop effective digitalization strategies. In today's world, digital technologies are changing not only the way we live, but also the way we manage our businesses and interact with customers.
Keywords: digitalization; agricultural sector; business processes; introduction of modern technologies; productivity; competitiveness